W obronie języka ojczystego – o pragnieniu zachowania narodowości w "Wieczorach pielgrzyma" Stefana Witwickiego - Stocka, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Celem artykułu jest przedstawienie stosunku Stefana Witwickiego do narodowości w jego Wieczorach pelgrzyma. W tym dziele autor wyraża zaniepokojenie językiem francuskim, którym Polacy coraz częściej posługują się także w swoich domach. Witwicki traktuje to jako zagrożenie dla polskiej kultury, którą jego zdaniem trzeba chronić, zwłaszcza w okresie niewoli. Pisarz postrzega język polski jako ważny element tożsamości narodowej, dbanie o język ojczysty uważa za szczególny wyraz wolności i niezależności wobec braku wolności politycznej. Witwicki próbuje przekonać rodaków, jak ważne jest kultywowanie polskich tradycji, niestety zauważa, że jego zalecenia nie są realizowane.

The aim of the article is to present the Stefan Witwicki’s attitude to nationality in his The Pilgrim’s Evenings [Wieczory pelgrzyma]. In this work the author expresses his concern about the French language, which is increasingly used by Poles, also in their homes. Witwicki treats it as a threat to Polish culture, which in his opinion needs to be preserved, especially during the time of captivity. The writer perceives the Polish language as an important element of national identity, he consideres taking care of the native language as a special expression of freedom and independence in the absence of political liberty. Witwicki is trying to convince his countrymen how important it is to cultivate Polish traditions, but unfortunately he notices that his recommendations are not implemented.
In defence of native language – about the desire to preserve nationality in 'The Pilgrim’s Evenings' by Stefan Witwicki
Keywords: Stefan Witwicki; Wieczory pielgrzyma; narodowość; język francuski; tradycja; The Pilgrim's Evenings; nationality; the French language; tradition